Transcriptomic analyses of intestinal gene expression of juvenile Atlantic cod (Gadus morhua) fed diets with Camelina oil as replacement for fish oil - Morais, Sofia; Edvardsen, Rolf B; Tocher, Douglas R; Bell, J Gordon (Comparative Biochemistry and Physiology Part B: Biochemistry and Molecular Biology, 2012)
For aquaculture of marine species to continue to expand, dietary fish oil (FO) must be replaced with more sustainable vegetable oil (VO) alternatives. Most VO are rich in n-6 polyunsaturated fatty acids (PUFA) and few are rich in n-3 PUFA but Camelina oil (CO) is unique in that, besides high 18:3n-3 and n-3/n-6 PUFA ratio, it also contains substantial long-chain monoenes, commonly found in FO. Cod (initial weight ~1.4 g) were fed for 12 weeks diets in which FO was replaced with CO. Growth performance, feed efficiency and biometric indices were not affected but lipid levels in liver and intestine tended to increase and those of flesh, decrease, with increasing dietary CO although only significantly for intestine. Reflecting diet, tissue n-3 long-chain PUFA levels decreased whereas 18:3n-3 and 18:2n-6 increased with inclusion of dietary CO. Dietary replacement of FO by CO did not induce major metabolic changes in intestine, but affected genes with potential to alter cellular proliferation and death as well as change structural properties of intestinal muscle. Although the biological effects of these changes are unclear, given the important role of intestine in nutrient absorption and health, further attention should be given to this organ in future.